Partie de l'Amérique septent? qui comprend la Nouvelle France ou le Canada - Robert de Vaugondy, Gilles, 1688-1766 (Creator); Groux, Charles Jacques (Contributor)
French map of New France and Atlantic Canada, published around 1799. Some of Ontario (including Lake Ontario) is visible, as is some of New England. Cities, towns, provinces, territories, regions, and bodies of water are named. An inset map in the lower left shows the Great Lakes. The locations of Indigenous communities are noted throughout the map, including the Iroquois, Inuit, Wyandot, Oneida, Algonquin, and Montagnais peoples (may be listed on the map by sub-group names or incorrect names). Relief shown pictorially. Scale is c 1:4,000,000. Published as part of Atlas universel. Corrigé et augmenté de la République française divisée on departemens. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .